Cloud seeding potential areas from remote sensing of low-level cloud and atmospheric water vapour / Siti Nabila Shamsul Anuar - Shamsul Anuar, Siti Nabila (2023)
Cloud seeding operations are carried out to increase the amount of precipitation due to drought phenomena that affect the availability of water for agricultural and industrial areas. Silver iodide compound (AgI) was used by dispersing it into clouds that act as ice nuclei and thus, alter the microphysical processes within the potential cloud. However, the success rate of cloud seeding operations in Malaysia is only 57 to 65 percent due to location and temporal factors. The low-level cloud and atmospheric water vapour (AWV) are parts of the main parameters contributing to successful precipitation from cloud seeding. Therefore, this study aims to determine the potential areas for cloud seeding operations based on low-level cloud distribution and AWV concentration in Peninsular Malaysia using MODIS satellite images. To achieve the aim of the study, the objectives of this project are: i) to integrate cloud masking and MODIS single reflective band methods for low-level cloud detection. ii) to compute the atmospheric water vapour concentration using the MODIS water vapour product. iii) to determine the potential areas for cloud seeding operation based on the distribution of low-level clouds and the AWV concentration. The potential areas were detected from the low-level cloud distribution and the concentration of AWV from remote sensing satellite images of Terra MODIS and mapped with GIS overlay operation. From the results, six (6) locations were found to be potential for cloud seeding operations located in Kemubu Agricultural Development Authority (KADA) in Kelantan, Muda Dam, Pedu Dam, Ah Ning Dam in Kedah, Durian Tunggal Dam, and Jus Dam in Melaka. The locations found were also coincidently used in previous cloud seeding operations conducted by the Malaysian Meteorological Department (MET) in 2019. The AWV concentration indicates a range between 4 cm to 7.2 cm from the previous locations of operations. Thus, the maps of potential areas based on low-level cloud and AWV for cloud seeding operations can be produced using Remote Sensing satellite images. The approach can potentially be utilised by related agencies such as MET to improve further and practically identify the appropriate time and areas for cloud seeding operations.